2011
DOI: 10.1063/1.3657156
|View full text |Cite
|
Sign up to set email alerts
|

Scanning photoelectron microscope for nanoscale three-dimensional spatial-resolved electron spectroscopy for chemical analysis

Abstract: In order to achieve nondestructive observation of the three-dimensional spatially resolved electronic structure of solids, we have developed a scanning photoelectron microscope system with the capability of depth profiling in electron spectroscopy for chemical analysis (ESCA). We call this system 3D nano-ESCA. For focusing the x-ray, a Fresnel zone plate with a diameter of 200 μm and an outermost zone width of 35 nm is used. In order to obtain the angular dependence of the photoelectron spectra for the depth-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…The interface chemical composition is probed nanoscopically by using three-dimensional high-resolution scanning photoelectron microscopy (3D nano-ESCA (electron spectroscopy for chemical analysis)) using a focused incident X-ray beam with a diameter of 70 nm and a photon energy of 1000 eV3031. The energy resolution of the spectrometer was set to 300 meV32.…”
Section: Resultsmentioning
confidence: 99%
“…The interface chemical composition is probed nanoscopically by using three-dimensional high-resolution scanning photoelectron microscopy (3D nano-ESCA (electron spectroscopy for chemical analysis)) using a focused incident X-ray beam with a diameter of 70 nm and a photon energy of 1000 eV3031. The energy resolution of the spectrometer was set to 300 meV32.…”
Section: Resultsmentioning
confidence: 99%
“…We performed scanning photoelectron emission microscopic (SPEM) measurements using a three-dimensional nanoscale electron-spectroscopy chemical analysis (3D nano-ESCA) system that was installed at BL07LSU of SPring-8. [14][15][16][17] The lateral and energy resolutions were set to 100 nm and 300 meV, respectively, at an excitation photon energy of 1000 eV. Figure 1 depicts wide scan photoelectron spectra that are obtained from four different positions (X = 0.1, 0.7, 1.2, and 1.8 µm from the SiC c-plane surface) of the trench sidewall, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…9 Scanning photoelectron microscopy (SPEM) involving photoemission spectroscopy (PES) with a nano-focused Xray probe is a powerful experimental technique for revealing the operation mechanism of nano-devices by observation of local changes in electronic structure. In our previous studies, we applied this SPEM technique 10 to ReRAM devices with Ni nanowires and found that on/off switching corresponds well to reduction and oxidation states. 11 We also have made the clear observation of p-type region formation around 500 nm thick at the metal electrode-graphene interface caused by Thomas-Fermi screening in a graphene FET.…”
mentioning
confidence: 95%
“…10 The lateral resolution and energy resolution at excitation photon energy of 1000 eV were set to 100 nm and 300 meV, respectively. In order to enable operando SPEM measurements during OFET operation, we developed a new sample holder with five independent electrodes including source, drain, gate, and two ground electrodes.…”
mentioning
confidence: 99%